Peran Knowledge Sharing dan Digital Competence dalam Meningkatkan Motivasi dan Kinerja Pengusaha Muda: Kerangka Kerja Konseptual dan Evaluasi Empiris - Hijrah Febriana Utami; Imran Ukkas; Rahmad Solling Hamid; Goso Goso (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
The purpose of this study was to examine the effect of knowledge sharing, digital competence, motivation and performance of young entrepreneurs. This research is a survey of 200 young entrepreneurs using the snowball sampling technique. Furthermore, validation and refinement tests were carried out, after which hypothesis testing was carried out using a structural equation model. The results show that there is a positive relationship between knowledge sharing, digital competence, motivation and performance of young entrepreneurs. In addition, motivation has a positive impact on the performance of young entrepreneurs. This study has revealed the relationship between knowledge sharing, motivation, and performance of young entrepreneurs as well as the indirect effect of motivational variables on the relationship between knowledge sharing, digital competence and performance of young entrepreneurs, which to the author's knowledge, has not been well explained in previous studies. This research produces practical implications, namely for practitioners and policy makers to be able to increase their understanding of knowledge sharing and be able to determine the right type of digital media as media that processes information, data, and other technological developments to support business activities.